PENGARUH SUBTITUSI PATI GANYONG (Canna edulis Ker.) TERHADAP KUALITAS KIMIA DAN ORGANOLEPTIK DODOL SUSU KAMBING - , KARDIAN ALISAFRI K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Milk Dodol is milk product made from glutinous rice flour, milk, and sugar. One of components of Milk Dodol is glutinous rice flour as a carbohydrate source (amylose) that responsible for the process of gelatinization. Canna starch has a higher amylose content than the glutinous rice flour, so that the gelatinization process will be faster. This research was aimed to observe the quality of goat milk dodol with substitution of canna starch. This research divided by two steps: first step analyzed the quality of raw materials to be used and second step was goat milk dodol making with substitution of canna starch 0, 25, 50, 75 and 100% with 3 replications each treatment. The data were statistically analyzed by one way design followed by Duncanâs new Multiple Range Test (DMRT). The substitution of canna starch increased the water, fat, and total carbohydrate content which increased quality of goat milk dodol (P<0.05) but it had no effect on its taste and aroma. Substitution of canna starch in goat milk dodol was the best level is 50% because resulted sweet taste, no goaty aroma, smooth texture, and high acceptability.